Transformasi Digital UMKM Melalui Sistem Pembayaran Elektronik: Studi Penerimaan dengan Model TAM - Andi Arfian; Juarni Siregar; Sigit Wibawa; Rahmiliasari Samnufida; Baginda Oloan Lubis (Pusat Riset dan Inovasi Nasional, 2024)
Digital transformation has become an essential approach for MSMEs to improve their operational efficiency and market competitiveness. This research investigates the acceptance of electronic payment systems among MSMEs using the Technology Acceptance Model (TAM). Data were obtained through questionnaires distributed to MSME respondents and analyzed using the bootstrapping technique to evaluate the significance of variable relationships. The findings reveal that Perceived Ease of Use (PEOU) has a significant impact on both Perceived Usefulness (PU) and Attitude Toward Using (ATU). Moreover, PU and ATU exert positive influences on Behavioral Intention (BI), with R² values of 0.65 for ATU and 0.71 for BI. These results suggest that the perceived ease of use and usefulness of electronic payment systems play a crucial role in shaping MSMEs’ attitudes and intentions toward adopting digital technologies. This study offers insights for formulating effective digital transformation strategies for MSMEs through the implementation of electronic payment systems.